A longitudinal study of the influence of social identity, outgroup exposure and affirmative action policy on first-year student academic success in the Economic and Management Sciences Faculty of Stellenbosch University - James, Liam (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.